The influence of second-row players on lumbar spine kinematics of front-row players during rugby union scrummaging - Cerrito, A.; Milburn, P.; Alston-Knox, C.; Evans, K. (Science & Sports, 2021)
Objectives In rugby union scrummaging, front-row players often sustain lumbar spine injuries, which can lead to physical impairments and absence from play. Poor lumbar spine posture adopted by front-row players during scrummaging may contribute to these lumbar spine injuries. However, few studies have investigated lumbar spine kinematics in front-row players during scrummaging and therefore little is known about what factors influence lumbar spine posture. The focus of this study was to determine whether interactions with other players affect front-row players` ability to adopt and/or maintain a neutral lumbar spine posture.